The Analysis of the UI/UX of Mobile Devices on the LAZNAS AL IRSYAD Website Using the User-Centered Design Method - Muhammad Ikhfil Khusen; Achmad Fauzan; Ridho Muktiadi; Mukhlis PrasetyoAji (Journal of ICT, Design, Engineering and Technological Science, 2024)
The research aims to analyze the User Interface (UI) and User Experience (UX) aspects of the LAZNAS (National Amil Zakat Institution) AL IRSYAD website, specifically when accessed via mobile devices. Employing a User-Centered Design (UCD) approach, the study places users at the core of the design process to identify their needs and the primary issues they encounter. The evaluation was carried out using the System Usability Scale (SUS) method to measure usability and user satisfaction. The findings revealed several shortcomings in the website's initial design, such as non-functional menu buttons, inconsistent icons, and poorly structured page layouts. The initial SUS score was 73.49, categorized as